Characterization of Recurrent and Sporadic Listeria monocytogenes Isolates from Raw Milk and Nondairy Foods by Pulsed-Field Gel Electrophoresis, Monocin Typing, Plasmid Profiling, and Cadmium and Antibiotic Resistance Determination - Harvey, J. (American Society for Microbiology, 2001)
Following previous surveys to assess the incidence of Listeria monocytogenes in raw milk and nondairy foods processed in Northern Ireland, isolates were characterized as recurrent or sporadic on the basis of multilocus enzyme electrophoresis (MEE) analysis and restriction fragment length polymorphism typing. In the present study, 45 representative recurrent and sporadic electrophoretic types (ETs) previously identified by MEE were subjected to pulsed-field gel electrophoresis (PFGE) of genomic DNA macrorestriction fragments, monocin typing, plasmid profiling, and an examination of resistance to cadmium and nine different antibiotics. Although PFGE proved to be capable of subdividing a number of recurrent and sporadic ETs, the grouping of strains arrived at by PFGE and MEE were in broad agreement, and previous conclusions regarding the designation of L. monocytogenes strains as recurrent or sporadic remained unaltered. It is considered that PFGE was able to detect minor genetic changes in recurrent ETs which occurred during the time period in which food surveys were carried out. Production of type E monocin (Types A to E were found among the 45 strains), plasmid carriage, and resistance to cadmium occurred more frequently in recurrent than in sporadic strains and may be important with regard to the ability of L. monocytogenes to persist in food and food-processing environments. Only 2 of 45 strains showed resistance to any of the nine antibiotics tested: two sporadic strains were resistant to tetracycline (MIC, 64 μg ml(−1)).